The Urban Garden City Shaping the City with Gardens Through History (Cities and Nature,, 2018)
This book provides an extensive interdisciplinary overview of the role of gardens in cities throughout different historical periods. It shows that, thanks to various forms of spatial and social organisation, gardens are part of the material urban landscape, biodiversity, symbolic and social shape, and assets of our cities, and are increasingly becoming valued as an 'order' to follow. Gardens have long been part of the development of cities, serving different purposes through the ages: shaping neighborhoods to promote health or hygiene, introducing aesthetic or biological elements, gathering the citizens around a social purpose, and providing food and diversity in times of crisis. Highlighting examples that can serve as the basis for comparisons, the chapters offer a brief panorama of experiences and models of gardens in the city - in the European context and in various periods of history - while also discussing issues related to garden cities, urban agriculture and community gardens. The contributors are university staff from various disciplines in the human and life sciences, in discourse with other academics but also with practitioners who are interested in experiences with urban gardens and in promoting an awareness of their spatial, social and 'philosophical' goals throughout history. The book will appeal to urban geographers, sociologists and historians, but also to urban ecologists dealing with ecosystem services, biodiversity and sustainable development in cities. From a more operational standpoint, landscape planners and architects are sure to find many of the projects enlightening and inspirational.